Photonic crystal fibre‐based polarimetric sensor for cure monitoring of magnetorheological smart composite material. Issue 15 (1st July 2014) - Ramakrishnan, M.; Rajan, G.; Semenova, Y.; Zhou, Y.; Jerrams, S.; Farrell, G.
Abstract : A buffer stripped high birefringent photonic crystal fibre based polarimetric sensor is developed for monitoring the curing process of magnetorheological elastomer (MRE) smart composite material. Using the developed sensor, different phases of the MRE curing process are clearly visible from the phase shift variation of the embedded polarisation maintaining photonic crystal fibre (PM‐PCF) sensor. During the curing process, the buffer stripped PM‐PCF exhibits a stress/strain induced phase shift variation from 0 to 1.98 rad. This is a significantly large phase change, which can be used to very clearly identify the different stages in the curing process. For comparison, a fibre Bragg grating sensor is also used for monitoring the internal strain during the curing process and its response does not allow one to reliably distinguish all the curing stages. The present investigation offers a simple non‐destructive method to monitor the curing process of MRE smart composite material.